EVALUATION OF REGIONAL Β CONVERGENCE IN EU COUNTRIES AT NUTS3 LEVEL - Pukelienė, Violeta; Butkus, Mindaugas (Ekonomika, 2012)
The paper deals with regional economic differences: theoretical aspects of their causes, evaluation methods, and presents in empirical analysis of the EU countries. The β convergence methods were applied for empirical research. The results suggest that in most of the EU countries, regions were diverging during 1995–2008. The recent territorial differences in the EU are determined not by the factors of countries or their groups, but by economic differences inside the countries.>